Climate change, agriculture, and potential crop yields in Central Asia - Thomas, Timothy S.; Akramov, Kamiljon T.; Robertson, Richard D.; Nazareth, Vijay; Ilyasov, Jarilkasin (International Food Policy Research Institute, 2021)
Agriculture in Central Asia is vulnerable to climate change due to rising aridity, declining availability of water resources for irrigation, and low adaptive capacity. We use climate data from CMIP5 with RCP8.5 for greenhouse gas emissions and the DSSAT crop model to investigate how yields of key crops in Central Asia will be affected by climate change. We distinguish changes in yields between spring and winter plantings, between irrigated and rainfed crops, and between crops grown with high and low amounts of fertilizer. The results suggest that countries (and areas within countries) that either have moderate summers or grow a number of crops in a relatively cold winter will benefit from climate change, while countries that grow many of the crops in the summer will experience losses.